In search of mound-builder histories. (15th September 2016) - Pauketat, Timothy R.
Abstract : There are insights to be gained from comparing three very different books on the mounds, mound-builders and moundvilles of later pre-Columbian and early historic-period eastern North America. These insights stem from the range of perspectives embodied by the trio of hardbacks here, written by authors with diverse backgrounds using very different kinds of case material. In one book, historian Terry Barnhart gives us a rich reading of the historical relationship of American archaeology to 'The Mound Builders', identified by many Euro-Americans in the late eighteenth and nineteenth centuries as an actual lost race or civilisation that pre-dated the American Indian occupation of the continent. In another book, writer Jay Miller seeks a cosmological explanation of all eastern North American mounds, in some ways reaffirming the centrality of mound building to Native identities. In a third volume, editor-archaeologists C. Margaret Scarry and Vincas Steponaitis, and 12 other authors, present the latest archaeological synthesis on Moundville, a great town in Alabama often cited as the civic-ceremonial core of a stereotypical Mississippian-era chiefdom ( c . AD 1120–1650). Tacking between the three texts, we might come to appreciate more clearly how we know, or might know, the mound-builder past by contextualising and theorising that past better than we are currently doing.